Anti-phospholipase A2 receptor antibodies directly induced podocyte damage in vitro. Issue 1 (31st December 2022) - Li, Yanfen; Yu, Juntao; Wang, Miao; Cui, Zhao; Zhao, Ming-hui
Abstract: Background: The pathogenesis of primary membranous nephropathy (MN) involves the antibodies against antigens on the cell surface of podocytes, with the majority of M-type phospholipase A2 receptor (PLA2R), and a profound podocyte dysfunction. The effects of anti-PLA2R antibodies directly to the podocytes remain unclear. Methods: Anti-PLA2R antibodies from patients with PLA2R-associated MN were affinity-purified using a column coupled with recombinant human PLA2R protein. Their effects on conditionally immortalized human podocytes were assessed by apoptosis assays, cellular calcium detection, wound healing assay, and immunofluorescent staining. Proteomics analysis was performed by LC-MS/MS and on PANTHER database. Results: The stimulation by anti-PLA2R antibodies could induce early-stage apoptosis of podocytes (MFI of Annexin V  = 104.3 ± 19.2 vs. 36.7 ± 7.6, p  = 0.004). The increase of calcium concentration in podocytes (MFI = 3309.3 ± 363.6 vs. 1776.3 ± 212.7, p  = 0.015) might attribute to the endoplasmic reticulum calcium efflux. The expression of calcium/calmodulin-dependent protein kinase IV (CaMK4) was also increased (MFI = 134.4 ± 9.8 vs. 105.3 ± 10.1, p  = 0.011). Proteomics results suggested that anti-PLA2R antibody treatment led to damage on cellular structure, and produced functional disorders on protein binding, actin filament binding, and microtubule motor activity. The staining of F-actin on foot process was reduced (MFI = 27.3 ± 2.8 vs. 47.5 ± 1.0, p  = 0.001) and the motility and adherence capacity of podocytes were reduced (number of migrated cells = 44.7 ± 3.1 vs. 53.3 ± 4.9, p  = 0.001) after incubation with anti-PLA2R antibodies. Conclusion: These data indicate that anti-PLA2R antibodies may directly induce podocyte damage independent of the complement system, which expands the mechanism of anti-PLA2R antibodies on MN.